Constrained Efficient Entrepreneurship - Allub, Lian (2018)
In the standard incomplete markets (SIM) model the risk of low future labor income (e.g., unemployment) generates precautionary savings. This way, the relation between capital accumulation and consumption insurance is positive. This is not necessarily the case if agents face entrepreneurship choice. Entrepreneurs face risky investment and might be willing to trade insurance for accumulation depending on their permanent ability across sectors, idiosyncratic shocks, and wealth. We study the welfare properties of an entrepreneurship choice model using the notion of constrained efficiency where a utilitarian planner dictates occupational choices and savings across risk-free and risky assets, while respecting individual budget constraints. We find that although the planner increases aggregate capital, a result shared with the SIM models, the planner changes the composition of aggregate capital and favors the accumulation of the risky capital employed by entrepreneurs at the cost of insurance. The planner also runs into more debt to finance a higher amount of entrepreneurs, lowering the entrepreneurship productivity threshold of the decentralized economy. All these results are based on a two-period model that we are currently extending to an infinite horizon and realistically calibrated economy. Finally, we investigate policies that can bring the competitive equilibrium allocations closer to the constrained-efficient planner. The set of policies that we plan to investigate include (i) the capitalization of unemployment benefits, (ii) tax reductions for new businesses, and (iii) a “second” chance clause that allows for retakes of (i) and (ii) after previous exits from entrepreneurship (i.e., failure). An extension of the model to the possibility of selling businesses is on the way.